2017
DOI: 10.14710/jitaa.42.2.59-65
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of meat quality in Bali cattle using ultrasound imaging

Abstract: The objective of this study were to predict carcass quality characteristics in Bali cattle using ultrasound imagery. The Number of samples were 81 heads of Bali cattle consist of bulls (62 heads) and cows (19 heads) with various age ranging from 1 to 6 years were collected their body weight and carcass qualities including backfat thickness (BF), longissmus dorsi thickness (LD), rump fat thickness (RF), rump thickness (RT), marbling score (MS) and the percentage of intramuscular fat (PIF). Those were estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
1
13
1
4
Order By: Relevance
“…In the study on marbling score using ultrasonic scanning method, Sri Rachma and Harada (2010) showed that the marbling score for Bali bulls at the age of 24 months was very low (0.17 to 0.20) (scale of 0 to 5 based on beef carcass grading standard of Japan). Likewise, by Jakaria et al (2017), the marbling score for Bali bulls at the age of 6 years and Bali cows at the age of 3 years were only 3.80±0.84 and 4.50±1.05, respectively (the scale of 0 to 9 based on AUS-MEAT/MSA marbling reference standards). Oematan (2000), did not find any marbling in all carcass of Bali cattle evaluated that were treated using high energy rations.…”
Section: Genetic Polymorphismmentioning
confidence: 96%
“…In the study on marbling score using ultrasonic scanning method, Sri Rachma and Harada (2010) showed that the marbling score for Bali bulls at the age of 24 months was very low (0.17 to 0.20) (scale of 0 to 5 based on beef carcass grading standard of Japan). Likewise, by Jakaria et al (2017), the marbling score for Bali bulls at the age of 6 years and Bali cows at the age of 3 years were only 3.80±0.84 and 4.50±1.05, respectively (the scale of 0 to 9 based on AUS-MEAT/MSA marbling reference standards). Oematan (2000), did not find any marbling in all carcass of Bali cattle evaluated that were treated using high energy rations.…”
Section: Genetic Polymorphismmentioning
confidence: 96%
“…In quality meat trait, Marbling Score (MS) of Bali cattle in one years old reached 1.92 (Jakaria et al, 2017). Measuring of MS based on AUS-Meat Standard.…”
Section: Resultsmentioning
confidence: 99%
“…imaging and the carcass (Jakaria, Khasanah, Priyanto, Baihaqi, & Ulum, 2017). Moreover, Liotta et al reported that the correlation between anatomic slices and ultrasonographic slices could be used to assess the feasibility of an ultrasound-guided epidural injection technique in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive organ size of the Sunda porcupine with ultrasonographical and photographical imaging was not significantly different ( p > .05) (Tables 1 and 2). The use of ultrasound to estimate the meat quality of the Bali cattle results in the correlation between ultrasound imaging and the carcass (Jakaria, Khasanah, Priyanto, Baihaqi, & Ulum, 2017). Moreover, Liotta et al (Liotta, Busoni, Carrozzo, Gabriel, & Bolen, 2015) reported that the correlation between anatomic slices and ultrasonographic slices could be used to assess the feasibility of an ultrasound‐guided epidural injection technique in dogs.…”
Section: Discussionmentioning
confidence: 99%